1997
DOI: 10.1103/physrevlett.78.1528
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of Dynamical Quasiparticle and Vertex Corrections in Optical Spectra

Abstract: The inclusion of dynamical quasiparticle effects lifts the underestimation of band gaps in semiconductors and insulators derived within density-functional theory. Simultaneously, they give rise to a remarkable reduction of the strengths of the quasiparticle peaks that is not observed in optical spectra. We show that dynamical contributions to the vertex corrections widely compensate the peak renormalization due to the dynamics in the quasiparticle formation. The slight reduction of the absorption spectrum yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 24 publications
5
67
1
Order By: Relevance
“…This is reflected in an underestimation of the loss intensity close to 8 eV, and might be due to the neglection of QP renormalization factors in Eq. (2) and to excitonic dynamical effects 21 . Despite this partial agreement in the 8 eV region, the present Ab-initio GW calculation is able to reproduce correctly the plasmon resonance.…”
Section: The Renormalized Plasmon Frequencymentioning
confidence: 99%
“…This is reflected in an underestimation of the loss intensity close to 8 eV, and might be due to the neglection of QP renormalization factors in Eq. (2) and to excitonic dynamical effects 21 . Despite this partial agreement in the 8 eV region, the present Ab-initio GW calculation is able to reproduce correctly the plasmon resonance.…”
Section: The Renormalized Plasmon Frequencymentioning
confidence: 99%
“…This approximation is often justified, since the plasma frequencies of the investigated systems are much larger than the excitonic binding energies. Moreover, it has been found that dynamical effects in the electron-hole screening and in the one-particle Green's function tend to cancel each other, at least in simple semiconductors (Bechstedt et al, 1997), which suggests that both should be neglected. This might not be true in other systems where the exciton binding energy is large.…”
Section: (I)mentioning
confidence: 99%
“…However, since it has been shown that dynamical effects in the electron-hole screening and in the one-particle Green function largely cancel each other, 33 this approximation is nevertheless valid, even if the relation E g ӷE b does not strictly hold.…”
Section: ͑17͒mentioning
confidence: 99%